2007
DOI: 10.1007/s10450-007-9023-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and adsorption investigations of zeolites MCM-22 and MCM-49 modified by alkali metal cations

Abstract: Ion exchange was made on MCM-22 and MCM-49 zeolites with different Si/Al molar ratios, with Li + , Na + , K + , and Cs + ions and the study of the influence of alkali metal cations on CO 2 adsorption properties was performed. The degree of ion-exchange decreased for larger cations (Cs + ) apparently due to steric hindrances. The exchange with different cations led to a decrease in the surface area and the micropore volume. Our study shows that the adsorption capacity of the tested zeolites depends significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…1) Textural properties of the MCM-22 zeolites used for CO 2 adsorption were determined from the nitrogen adsorption data published in the foregoing paper (Pawlesa et al 2007). The main texture parameters, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Textural properties of the MCM-22 zeolites used for CO 2 adsorption were determined from the nitrogen adsorption data published in the foregoing paper (Pawlesa et al 2007). The main texture parameters, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Although extensive experimental and theoretical works on the adsorption of CO 2 on different zeolites were published, to our knowledge there is only one report concerning the isothermal study of CO 2 adsorption on MCM-22 zeolite (Pawlesa et al 2007). This zeolite (IZA code MWW) crystallizes as thin sheets or plates and has unique and unusual structure (Rubin and Chu 1990;Lawton et al 1998).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to this work, Zukal showed that the CO 2 adsorption capacities of MCM-49 (MWW) derivatives varied with changes in the cation type and the aluminum amount, with the Na-exchanged MCM-49 with the highest aluminum content exhibiting the maximum CO 2 adsorption. [35] The CO 2 adsorption properties of zeolites are also influenced by the porous characteristics of the framework. From a comparative study of the CO 2 adsorption capacities on a number of commercially available zeolites including 4A, 5A (both LTA), 13X, APG-II, and WE-G 592 (all FAU), Siriwardane reported that the highest adsorption capacities were observed in zeolite 13X, the material with the largest pore diameter and volume among those studied.…”
Section: Inorganic Adsorbentsmentioning
confidence: 99%
“…On the contrary, aminegrafting on zeolites resulted in an increase in CO 2 /N 2 selectivity, and more elevated heats of CO 2 adsorption implied a strong reduction in CO 2 capture capacity. Specifically, NH 2 -ITQ-2 showed exceptionally high CO 2 /N 2 selectivity combined with the best separation capacity among the studied MWW-type zeolites [157][158][159][160][161].…”
Section: Other Processesmentioning
confidence: 99%